Mechanical analysis of the effects of different mechanical alloying periods on Ni3Al intermetallic compound fabrication quality - Tan, Kim Han; Johan, Mohd Rafie; Ahmad, Roslina; Kadri, Nahrizul Adib; Zain, Norita Mohd; Arof, Abdul Kariem (Electrochemical Science Group, 2012)
Ni and Al elemental powder mixtures with composition Ni75Al25 (at ) were mechanically alloyed in a planetary ball mill under different mechanical alloying (MA) durations. X-ray diffraction (XRD), scanning electron microscope (SEM) and simultaneous thermal analysis (STA) were conducted to study phase transformations, morphology changes and thermal property of Ni-Al mixture during MA. Ni3Al intermetallic compound was formed successfully after 10h of milling, which was the shortest formation period that ever reported for this intermetallic compound. The nanocrystalline Ni3Al with the lowest crystallite size of 12.6nm was synthesized. Refinement of crystallite size with increasing internal strain was significant as milling duration was increased gradually. During formation of the Ni3Al, the powder particles have undergone incidents of welding, microforging, fracturing, rewelding and agglomeration.